Falling of asparagus flowers (Asparagus officinalis Linneo.) for the handling of Prodiplosis longifila Gagné in the irrigation of the Chavimochic project - Prado, S. (2018)
The asparagus, a dioecious plant, usually includes plants of both sexes, though also hermaphrodite ones. The male inflorescences are frequented by adult Prodiplosis longifila, who lay such large amounts of eggs on them that its populations can reach millions of individuals over a lapse of 20 to 30 days, which is the plant regular flowering period. The field investigation took place in two locations: (i) the Irrigation Research Unit of the Universidad Nacional Agraria La Molina (UNALM) and (ii) properties of the Agricultural Society of Virú (SAVSA). The number of fallen flowers and larvae per bud after applying multiple treatments on asparagus plots of the two locations was counted to determine the best concentration and application time of various fertilizers to induce the highest percentage of flower fall to manage P. longifila populations. In the UNALM the fertilizer B Dose 2 generated the highest percentage of fallen flowers, 82.1 % ± 14.85 %, and the fertilizer C Dose 1 caused 74.94 % ± 13.78 %. In SAVSA the fertilizer B Dose 3 made a percentage of fallen flowers of 50.6 % ± 21.56 % and fertilizer B Dose 2, 49.85 % ± 16.28 %. The average number of P. longifila 2nd-stage larvae, evaluated on fifteen flowers and in three moments was 3.9 larvae. Foliar fertilizers applications affected both male and female flowers almost equally in all treatments, percentage-wise. Foliar fertilizers promote asparagus flowers falling, consequently contribute to a significative reduction of P. longifila populations, due to a larvae exposition to rapid desiccation under the sun.